SPE Reservoir Simulation Symposium 2001
DOI: 10.2118/66378-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Miscible WAG Injection EOR in the Magnus Field

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe viability of miscible WAG injection as an EOR scheme for the Magnus reservoir is under consideration. Performance prediction and optimization under this type of recovery mechanism, in which the residual oil is usually recovered by a multi-contact miscible (MCM) process, rely mostly upon compositional simulation. Unfortunately, numerical dispersion effects, associated with large grid blocks required in field scale compositional simulation of MCM processes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The gasisenriched atthe Sullom Voeterminalbyinjection ofpropanea ndb utane.The target molecularw eightfor the injection gasis2 1 ( Lee etal. 2001;Haajizadeh etal. 2001).…”
Section: The Eor Opportunitymentioning
confidence: 99%
“…The gasisenriched atthe Sullom Voeterminalbyinjection ofpropanea ndb utane.The target molecularw eightfor the injection gasis2 1 ( Lee etal. 2001;Haajizadeh etal. 2001).…”
Section: The Eor Opportunitymentioning
confidence: 99%
“…Previous research on WAG for immiscible and CO 2 floods has shown that WAG can cause a significant increase in oil recovery primarily because of improved sweep efficiency based on changes in mobility contrasts (Sanchez, 1999;Haajizadeh et al, 2001;Jarrell et al, 2002). WAG may also reduce the amount of gas injection required, although determining the optimum WAG parameters is sometimes difficult and reservoir dependent.…”
Section: Wag Optimization For Shallow Enriched Gas Floodsmentioning
confidence: 99%
“…Stalkup also showed that simultaneous grid refinement in horizontal and vertical 52 directions caused numerical dispersion to overestimate the recovery with gas enrichment beyond the MME (Stalkup et al 1990;Stalkup, 1990; Stalkup, 1987). Other researchers have also examined the effect of viscous crossflow, capillary pressure, diffusion, gravity, heterogeneities, and numerical gridding on recovery (Lim et al, 1997;Lim, 1993;Fayers, 1992; Solano et al, 2001a).Previous research on WAG for immiscible and CO 2 floods has shown that WAG can cause a significant increase in oil recovery primarily because of improved sweep efficiency based on changes in mobility contrasts (Sanchez, 1999;Haajizadeh et al, 2001;Jarrell et al, 2002). WAG may also reduce the amount of gas injection required, although determining the optimum WAG parameters is sometimes difficult and reservoir dependent.…”
mentioning
confidence: 99%
“…1,2 This trend has been fueled by enhancements in hardware, software and geologic modeling and reservoir simulation technologies. More specifically, the abilities to create large geologic models are being driven by faster computer processors with access to more memory, better methods for representation of complex geology, improvements in surface, framework, geocellular and geostatistical modeling and easier to use software.…”
Section: Traditional or Deterministic Workflowsmentioning
confidence: 99%